The sense of order : a study in the psychology of decorative art - E H Gombrich (Ithaca, N.Y. Cornell University Press, 1979)
Investigates the psychology of decorative design and the creation and function of formal orders concentrating on problems of decorative theory, visual perception, and the symbolism of design.
Keywords: Decoration and ornament --. -- .; Psychological aspects; Art décoratif; Aspect psychologique; Decoracao